For a social cartography of enconunters - Rocha, Eduardo (2017)
This article results from the encounter and experience with the Social Cartography Methodology by Brazilian and Argentinean research groups, composed of architects, urban planners, and geographers in the Dunas neighborhood, within the periphery of Pelotas, in the Southernmost Brazil state of Rio Grande do Sul. The methodology of Social Cartography followed the weaving of the city, the interrelationships of the particular case of the Dunas neighborhood, line-by-line, in the sewing of the daily life, desires, problems, solutions, and public authorities' actions. The text seeks to raise issues related to the Social Cartography method, such as organization, analysis, and forms of applications. It also points to emancipatory and communitarian aspects involved in this process. We propose that Social Cartography can help to weave the city, undoing the dichotomy between center and periphery while new social spaces are produced from intervention research.